2019
DOI: 10.2141/jpsa.0180131
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Studies on Red Junglefowl (<i>Gallus gallus</i>) and Native Chicken (<i>Gallus gallus domesticus</i>) in Samar Island, Philippines using the Mitochondrial DNA D-Loop Region

Abstract: A study was conducted to provide genetic information on the matrilineal phylogeny and genetic diversity of Red junglefowl (RJF) and native chickens in Samar Island, Philippines and to identify the genetic distance between Philippine junglefowls and other RJF species in Southeast Asia using complete mitochondrial DNA D-loop sequences. A total of 5 RJFs and 43 native chickens from Samar Island were included in this study. The results showed that Samar RJFs had a nucleotide diversity of 0.0050±0.0016, which was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Although, this is a small study including only two breeds, it Other mitochondrial markers such as D-loop (control region) have also been used by various investigators to explore diversity among different native chicken breeds across the world. Higher number of polymorphic sites defining more number of haplotypes were reported in Samar Philippines native chickens (17 and 5) [17], Hungarian native chickens (17 and 11) [18], Egyptian native chickens (28 and 18) [19], native chicken breeds of Jiangsu (33 and 19) [20], and chicken breeds of Korea (84 and 31) [21]. These studies showed high genetic diversity with higher haplotype and nucleotide diversity in Samar Philippines native chickens (0.92 and 0.0056) [22], Hungarian native chickens (0.626 and 0.0049) [18], Egyptian native chickens (0.81 and 0.0045) [19], native chicken breeds of Jiangsu (0.862 and 0.00591) [20], and chicken breeds of Korea (0.604 and 0.007) [21].…”
Section: Discussionmentioning
confidence: 82%
“…Although, this is a small study including only two breeds, it Other mitochondrial markers such as D-loop (control region) have also been used by various investigators to explore diversity among different native chicken breeds across the world. Higher number of polymorphic sites defining more number of haplotypes were reported in Samar Philippines native chickens (17 and 5) [17], Hungarian native chickens (17 and 11) [18], Egyptian native chickens (28 and 18) [19], native chicken breeds of Jiangsu (33 and 19) [20], and chicken breeds of Korea (84 and 31) [21]. These studies showed high genetic diversity with higher haplotype and nucleotide diversity in Samar Philippines native chickens (0.92 and 0.0056) [22], Hungarian native chickens (0.626 and 0.0049) [18], Egyptian native chickens (0.81 and 0.0045) [19], native chicken breeds of Jiangsu (0.862 and 0.00591) [20], and chicken breeds of Korea (0.604 and 0.007) [21].…”
Section: Discussionmentioning
confidence: 82%
“…The haplotypes of haplogroups A and/or CD that were observed in 15 populations of indigenous chickens and red junglefowl in Thailand were similar or closely related to the representative haplotypes in South China, Vietnam, Laos, Sri Lanka, and Japan 5 . Some haplotypes of haplogroups F and J, which are minor haplogroups found only in limited areas of Southern China and Southeast Asia 4 , 5 , 21 , 22 , 29 , were also found in Thai indigenous chickens. However, 29 unknown haplotypes were newly identified in the present study, with 14 and 17 identified in indigenous chickens and red junglefowl, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…To determine the phylogenetic positions of red junglefowl and indigenous chickens from Thailand in chicken populations throughout the world, Bayesian and ML phylogenetic trees were constructed using BEAST v2.4.3 38 and PhyML v3.0 39 respectively, including 420 D-loop sequences (A01, A02, …Y and Z) obtained from GenBank, which were defined by Miao et al 5 (Supplementary Table S6 ). In addition, 22 D-loop sequences obtained from GenBank were used for analysis (KY039406 and KY039428 in Herrera et al, 2016, direct submission to the international database GenBank; MN013407 in Peng et al, 2019, direct submission to the international database GenBank; other sequences are cited in Supplementary Table S6 ) 21 , 22 , 40 48 . The best-fit substitution model of the D-loop sequences was determined based on the Bayesian Information Criterion using jModeltest v2.1.10 49 , 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Genetic diversity and relationships among chicken breeds have been studied widely in the past decade using mitochondrial sequences [ 6 12 , 18 , 22 ]. This current study is the first to address the origin of the Tosa-Jidori breed, indigenous to Kochi Prefecture, using complete D-loop and mitogenome sequences.…”
Section: Resultsmentioning
confidence: 99%
“…However, their study was based on mitochondrial DNA D-loop sequence only, and they used limited numbers of global chicken samples other than JNC. Most studies of chicken mitochondrial DNA have also relied on D-loop sequencing [ 7 12 ]. The small size (about 1,230 bp) of the D-loop limits the resolution of the maternal phylogeny.…”
Section: Introductionmentioning
confidence: 99%